TADLIS AND TAGHRIR IN TRANSACTIONS IN THE E-MARKETPLACE - Trisnaning Setya Sutjipto; Eko Fajar Cahyono (Universitas Airlangga, 2020)
This study aims to determine whether or not there are transactions that contain elements of tadlis and tagririr in the e-marketplace. This study uses primary data obtained from e-marketplace consumers in Surabaya which are classified as the age generation Z category. This study uses a descriptive quantitative approach with survey methods and questionnaires. The results of this study found that there are transactions in the e-marketplace that contain elements of tadlis and taghrir. Transactions with the tadlis element get a high response while transactions with the taghrir element get a lower response.Keywords: Market Distortion, Tadlis, Taghrir, E-MarketplaceREFFERENCE Afzalurrahman. (1996). Doktrin ekonomi Islam. Yogyakarta: Dana Bhakti Wakaf.Al Arif, M. Nur Rianto dan Euis Amalia. (2010). Teori mikroekonomi: Suatu perbandingan ekonomi islam dan ekonomi konvensional. Jakarta: Kencana.Angga, K. P. et al. (2017). Rancang bangun aplikasi marketplace penyedia jasa les private di kota Pontianak berbasis web. Jurnal Sistem dan Teknologi Informasi, 2 (5), 1-5. Codrington, G. & Grant-Marshall, S., Penguin. (2004). Mind the gap. South Africa: Penguin.David. (2014). E-Marketplace Sebagai Penyedia Layanan Penjualan Barang. Konferensi Nasional Sistem Informasi 2018, 159-164.Dewa, B. P. & Setyohadi, D. B. (2017). Analisis dampak faktor customer relationship management dalam melihat tingkat kepuasan dan loyalitas pada pelanggan marketplace di Indonesia, TELEMATIKA, 14(1), 33 – 38.Fauzi, Ahmad Sofwan. (2017). Transaksi jual-beli terlarang; ghisy atau tadlis kualitas. MIZAN: Journal of Islamic Law, 1(2), 143-154.Farki, A., Baihaqi, I., & Wibawa, B. M. (2016). Pengaruh online customer review dan rating terhadap kepercayaan dan minat pembelian pada online marketplace di Indonesia. Jurnal Teknik ITS, 5(2), 614-619.Firdayanti, Restika. (2012). Persepsi risiko melakukan e-commerce dengan kepercayaan konsumen dalam membeli produk fashion online. Journal of Social and Industrial Psychology, 1(1), 1-7.Grail Research. (2011). Consumers of tomorrow insights and observations about generation Z.Hakim, Lukmanul. (2017). Distorsi pasar dalam pandangan ekonomi Islam. Ekomadania, 1(1), 1-15.iPrice insight. (2019). Peta E-Commerce Indonesia 2019. (www.iprice.co.id).Karim, Adiwarman A. (2018). Ekonomi Mikro Islam. Depok: PT Rajagrafindo Persada.Laporan Survei Asosiasi Penyelenggara Jasa Internet Indonesia. (2019). Penetrasi & profil perilaku pengguna internet Indonesia 2018. (www.apjii.or.id)Manalu, A. S. B., Sumarwan, U., & Suroso, A. I. (2007). Analisis faktor - faktor yang mempengaruhi kepuasan pelanggan online. Jurnal Manajemen dan Agribisnis, 4(2), 67-80.Penulis (2018). Jawa masih mendominasi penetrasi E-Commerce Indonesia. (www.databoks.katadata.co.idPratama, Hellen Chou. (2012). Cyber smart parenting. Bandung: PT. Visi Anugerah Indonesia.Pusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI). (2015). Ekonomi Islam. Jakarta: Rajawali Pers.Putra, N.P dan Panto, Y. J. (2012). Aplikasi E-marketplace berbasis web 2.0. Skripsi tidak diterbitkan. Palembang: STMIK GI MDP.Sarwono, J. 2006. Metode penelitian kuantitatif dan kualitatif. Yogyakarta: Graha Ilmu.Sudjana, Nana & Ibrahim. (1989). Penelitian dan penilaian pendidikan. Bandung: Sinar Baru.Sugiyono. (2019). Metode penelitian pendidikan (kuantitatif, kualitatif, kombinasi, R&D, dan penelitian pendidikan). Bandung: Alfabeta.Singarimbun, Masri & Effendi, Sofian. (1995). Metode penelitian survei. Jakarta: PT Pustaka LP3ES.Tempo.co. (2017). Riset Google: Warga Surabaya Paling Banyak Belanja Online. (www.tempo.co).